2021
DOI: 10.1155/2021/3804379
|View full text |Cite
|
Sign up to set email alerts
|

Zanthoxylum zanthoxyloides Alkaloidal Extract Improves CCl4-Induced Hepatocellular Carcinoma-Like Phenotypes in Rats

Abstract: Background. Despite the enrollment of new small molecules such as Sorafenib for the treatment of hepatocellular carcinoma (HCC), HCC still remains a significant contributor to cancer-related mortality and morbidity globally. Zanthoxylum zanthoxyloides is long suspected of possessing anticancer bioactive compounds that may hold the prospect of adjunctive therapy against inflammation-related cancers such as HCC. Objective. This study assessed the effects of an alkaloidal extract of the leaves of Zanthoxylum zant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Trichloromethyl peroxyl radical induces lipid peroxidation and oxidative stress as a result of the generation of endogenous lipid radicals from unsaturated fatty acids within membranes of hepatic cells [ 24 ]. When the liver damage due to the generation of endogenous lipid radicals proceeds without treatment, it sets in motion a number of pathological transformations leading to the establishment of HCC-like phenotypes in rats [ 26 ]. Thus, to assess the prophylactic hepatoprotective and anti-HCC effects of LPE, three functional hallmarks of the liver, namely, metabolic, biosynthetic, and detoxification were monitored using endpoints such as survival rate, body weight changes, gross liver anatomy, liver histology, biochemical parameters ( α -fetoprotein, C-reactive protein, albumin, total protein, prothrombin time, AST, ALT, ALP, GGT, and bilirubin), and hematological assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Trichloromethyl peroxyl radical induces lipid peroxidation and oxidative stress as a result of the generation of endogenous lipid radicals from unsaturated fatty acids within membranes of hepatic cells [ 24 ]. When the liver damage due to the generation of endogenous lipid radicals proceeds without treatment, it sets in motion a number of pathological transformations leading to the establishment of HCC-like phenotypes in rats [ 26 ]. Thus, to assess the prophylactic hepatoprotective and anti-HCC effects of LPE, three functional hallmarks of the liver, namely, metabolic, biosynthetic, and detoxification were monitored using endpoints such as survival rate, body weight changes, gross liver anatomy, liver histology, biochemical parameters ( α -fetoprotein, C-reactive protein, albumin, total protein, prothrombin time, AST, ALT, ALP, GGT, and bilirubin), and hematological assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products have been widely reported for their cytotoxic effects by acting as antioxidants, anti-proliferative, and/or apoptotic agents [ 46 ]. A recent study explored the novel role of phytochemicals in overcoming resistance to chemotherapy and sensitizing cancer cells to different anticancer drugs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, it was observed that PCFHE exerts bacteriostatic effects against the test microorganisms over a period of 6-24 hours ( Figure 7 ). The bioactivity of medicinal plants has always been attributed to their phytochemical composition and functional group enrichment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%